PENERAPAN PENDEKATAN EXPERIENTIAL LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPA - Sartini, - (WAHANA PEDAGOGIKA, 2016)
The material of Science in identifying the function of human respiratory organ was considered to difficult by the students. This could be seen from the 11 students who achieve 70% or more only 5 students or 45.45% of students who achieve the mastery minimal value. Therefore, to improve the learning outcomes it will use experiential learning model. The purpose of this study was to know the effect the application of Experiential Learning model to the learning achievement of Science. The conclusion from this research that the implementation of experiential learning model gave a positive impact on increasing the understanding of Science material in identifying the function of human respiratory organ at the fifth graders of the second state elementary school Sidomuiyo, the evidence wasÂ  there is an improving of the studentsâ learning outcomes, i.e. the first cycle (63.63%), and the second cycle (81 , 81%) and the absorption of students on average of 70.90 into 84.54.